A further step towards stabilising the nomenclature associated with the genus name Aloe (Asphodelaceae subfam. Alooideae): the legitimate name A. perfoliata and the illegitimate name A. mitriformis are based on the same type, with notes on the identity of A. mitriformis - Smith, Gideon F.; Klopper, Ronell R.; Woudstra, Yannick; Grace, Olwen M. (Phytotaxa, 2025)
Despite having received significant taxonomic attention over the past more than two-and-a-half centuries, aspects of the nomenclature associated with the genus name Aloe (Asphodelaceae subfam. Alooideae), including its typification, remain in flux. This partly came about because of disparate interpretations of the application of the names A. perfoliata and A. mitriformis. We show that historically these two names have been applied to two morphologically very different taxa. The current (and historical) taxonomic concept associated with the name A. mitriformis is beyond doubt and the name, albeit illegitimate, is applicable to a large-growing, creeping species with stems of up to 2 m long and rather dense, many-flowered capitate inflorescences from southwestern South Africa. A recent attempt to typify the name A. mitriformis on a plate, Fig. 19, t. 17 [with the accompanying text on p. 21], published in 1732 in volume 1 of Hortus elthamensis by Johann Jacob Dillenius (1684–1747) was not effective because the name A. mitriformis is homotypic with the name A. perfoliata. The type of the name A. perfoliata, as well as that of the name A. mitriformis, is an herbarium specimen that consists of a single sparsely-flowered, cylindrical raceme. The name A. perfoliata cannot confidently be applied to material of any known aloe. Yet, the type of the name A. perfoliata is unambiguously the type of the genus name Aloe. The taxonomic concept to date associated with the name A. mitriformis cannot be reconciled with the type of the name A. perfoliata and, furthermore, the name A. mitriformis is not a heterotypic synonym of A. perfoliata. We here record that the name A. mitriformis is illegitimate because it was, arguably inadvertently, but in effect, published as a superfluous synonym for the legitimate name A. perfoliata by Philip Miller (1691–1771). However, we do not advocate adopting a later, validly published and legitimate name in the stead of the name A. mitriformis because a proposal to conserve this name has been accepted for consideration by the General Committee and distribution to and consideration by the Permanent Nomenclature Committee for Vascular Plants.